Analysis of essential oils isolated by steam distillation from Swinglea glutinosa fruits and leaves (2015)
Essential oils obtained by steam distillation from Swinglea glutinosa (Blanco) Merr. fruit peel or leaves were analyzed by gas chromatography with flame ionization and mass spectrometry detection systems. A total of sixtyseven compounds were found, sixty-four of which were common to both oils, although present in different relative amounts. The main component of the essential oils obtained from S. glutinosa fruit peel or leaves was trans-nerolidol (19.1% and 28.4%, respectively). Sesquiterpene hydrocarbons (50%) and their oxygenated analogues (35%) were the most abundant compound types in the leaf oil. Monoterpene hydrocarbons (51%) were the principal compound family found in the oil obtained from fruit peels.